Making sense of fashion involvement among Malaysian Gen Y and its implications / Carol Teo Boon Chui, Nur Suhaila Nik and Nurul Fatin Azman. - Teo, Carol Boon Chui; Nik, Nur Suhaila; Azman, Nurul Fatin (Universiti Teknologi MARA Selangor, 2017)
In keeping pace with globalization of the fashion retail industry, fashion retailers are expanding aggressively across Asia. Malaysia is no exception with clothing market demand expected to double from USD3.6 million in 2011 to USD7 million in 2018. New foreign retail brands have mushroomed to compete alongside local brands to cater to the fashionable aspired yet unique Gen Y. This study dwells into determinants of fashion involvement of Malaysian Gen Y. They appear to have an insatiable appetite for the quick and trendy lines although less interested in logo-centric clothes and want unbranded goods, dressing for self-identity. They have blur distinctions as compared to earlier generations where dressing is seen as a way to fit in. Given their blurring fashion identity, local fashion retailers find it increasingly difficult to understand this ever-evolving customer base. Methodology involved mixed methods with storefront observations and interviews with top local fashion retailer. Using mall intercept approach, Gen Y were sampled via survey questionnaires. Findings were contrary to other studies. Fashion knowledge was the only dominant and significant factor. Local brand confidence, fashion shopping style and patronage behaviour were nonsignificant predictors. Implications on fashion retailing and theoretical implication on fashion involvement are debated.